Hydrostatic Reduction With Barium Enema Is A Preferred Treatment Option for Uncomplicated Intussusception : Five Years Experience in Cmch - Bhuiyan, Md Akbar Husain; Chowdhury, Tanvir Kabir; Chowdhury, Tahmina Akhtar; Rahman, MA Mushfiqur; Farooq, Md Abdullah Al; Sajid, Md Minhajuddin; Sarwar, Khurshid Alam; Khastagir, Rajib; Habib, Md Golam; Banu, Tahmina (Journal of Chittagong Medical College Teachers' Association, 2015)
Intussusception is a common cause of intestinal obstruction in young children and is a common emergency in infants and children. Hydrostatic reduction of intussusception is a less invasive procedure for both diagnosis and treatment of it. We describe our experience with hydrostatic reduction of intussusception. A retrospective review of the patients of Intussusception admitted in the department of Pediatric Surgery Chittagong Medical College Hospital (CMCH) Chittagong, Bangladesh from January 2009 to December 2013 was done. Patients underwent hydrostatic reduction were evaluated separately. Data were analyzed with regard to success and failure of hydrostatic reduction, necessitating laparotomy, complication and mortality. There were 231 patients of Intussusception. Age range was lmonth to 15 years with median age of 8 months. Male to Female ratio was 2.9:1. Mean duration of presentation was 40 hours after onset of symptoms. Hydrostatic reduction was attempted in 142 patients and was successful in 107 patients, 35 patients needed surgery in whom per-operative manual reduction was done in 28 patients and intestinal resection anastomosis was done in in 7 patients. There were 2 cases of recurrence following hydrostatic reduction and no case of perforation due to hydrostatic reduction. 2 patients died following JCMCTA 2015 ; 26 (1) : 9-13